Development of an Efficient Process for a Key Synthetic Intermediate of the SGLT2 Inhibitor LH-1801 - Qu, Jun; Hu, Zhong; Zhang, Pengcheng; Wu, Hongxiang; Xue, Honglan; Cai, Lei; Sun, Xingxing; Qian, Yun; Peng, Rongrong; Gao, Dehua (Pharmaceutical Fronts, 2025)
(2-Bromo-5-chloro-4-((5-ethylthiophen-2-yl)methyl)phenyl)methanol (1) is a key intermediate of the SGLT2 inhibitor LH-1801. This study aimed to explore an efficient process for the synthesis of 1 on a large scale. In this work, the synthetic route started with 3-amino-4-methylbenzoic acid methyl ester (2), followed by (1) bromination, (2) diazotization–Sandmeyer reaction, (3) the oxidation of the benzylic hydrogen to give the corresponding benzoic acid, (4) Friedel–Crafts acylation, and (5) reduction of a carbonyl group (C = O) into a methylene group (–CH2–) to achieve the target product. We optimized the diazotization-Sandmeyer reaction conditions and reaction parameters for a successful oxidation sequence. In addition, a reduction system for Step 5 was screened. With the optimal reduction system (NaBH4/BF3•THF) in hand, the target product (1) could be generated in an efficient and concise one-step reduction approach. Given the above, the synthesis route with process optimization delivered the target product (1) in only five steps with an overall yield of 18.9% and a purity higher than 99%.
Keywords: SGLT2 inhibitor; LH-1801; diabetes; sodium borohydride; boron trifluoride